Noradrenergic Inhibition of Midbrain Dopamine Neurons - Paladini, Carlos A. (J Neurosci, 2004)
Receptors that couple to phosphoinositide hydrolysis, which include metabotropic glutamate receptors (mGluRs) and muscarinic receptors, are known to either activate or inhibit the activity of dopamine cells depending on the pattern of receptor activation. Transient activation of α(1) adrenoceptors with norepinephrine (NE) resulted in an outward current in midbrain dopamine neurons recorded in brain slices. The NE-mediated outward current was induced by activation of a potassium conductance through release of calcium from intracellular stores. Unlike the mGluR-mediated outward current, the outward current induced by α(1) adrenoceptors often consisted of multiple peaks. Activation of α(1) adrenoceptors also induced a wave of calcium release that spread through the soma and proximal dendrites without a decline in amplitude or rate of propagation and therefore differed qualitatively from that induced by mGluRs. Finally, the α(1) adrenoceptor-activated outward current was more sensitive to the calcium store-depleting agents ryanodine and caffeine. Thus, although bothα(1) adrenoceptors and mGluRs mobilize calcium from intracellular stores, the mechanisms and pools of calcium differ. The results suggest that noradrenergic innervation of dopamine cells can directly inhibit the activity of dopamine cells. Psychostimulants, such as amphetamine, will therefore have a direct effect on the firing pattern of dopamine neurons through a combination of actions on dopamine and α(1) adrenoceptor activation.